Substantive law: resources workbook - Turner, Chris (Hodder & Stoughton Educational Limited, London, 2000)
Chris Turner's "Substantive Law: Resources Workbook" serves as an invaluable companion for students and practitioners navigating the complexities of substantive law. This workbook provides a comprehensive collection of resources designed to enhance understanding and application of legal principles. Turner's approach integrates theory with practical examples, offering readers a structured pathway to mastering substantive law concepts. Whether used for self-study or in academic settings, this workbook proves essential for anyone seeking a deeper comprehension of legal principles and their real-world implications.
This text covers all criminal, contract and tort elements of the A Level syllabus. It provides extracts from primary sources and other material and articles, together with exercises for students to develop their understanding of the topics.
Keywords: Application of Law; Legal Principles